An introduction to modeling of transport processes : applications to biomedical systems - Datta, Ashim K. (Cambridge texts in biomedical engineering., 2010)
"Organized around problem solving, this book gently introduces the reader to computational simulation of biomedical transport processes, bridging fundamental theory with real-world applications. Using this book the reader will gain a complete foundation to the subject, starting with problem simplification, implementation in software, through to interpretation of results, validation, and optimization"--Provided by publisher.